Empowerment of schools in efforts to prevent violence among adolescent students in West Sulawesi - Risnah, Risnah (PABBURA : Health Service Journal, 2024)
Youth violence refers to acts of violence among individuals aged 10–29 who have no family ties, whether they know each other or not. It usually occurs outside the home and includes various forms of action, such as online or offline intimidation, physical clashes, to more severe sexual and physical violence. The impact of this violence includes the risk of death, injury, and disability, as well as long-term health consequences, including mental health problems and risky behaviors that can lead to chronic disease. Youth violence is also associated with high school dropout rates, negatively affects cognitive development, and reduces opportunities to make positive contributions to society. The aim of this community service activity is to prevent acts of violence in schools through empowerment efforts. The empowerment methods used include outreach, in-depth interviews and surveys of teachers and students about violence. The series of activities shows that the school welcomes the series of community service activities as a form of empowering the school in preventing acts of violence. Bullying and student fights are forms of violence that often occur in schools. A series of outreach activities in the form of interviews and surveys using questionnaires can provide initial information on the school’s understanding of violence and basic knowledge about violence among students and teachers that still needs to be improved.